ANALYSIS OF WIND AND SEA CURRENT HYBRID POWER PLANT - Kusuma Nugraha, Fahri
The territory of Indonesia has a very large potential for wind energy and ocean currents. However, this potential cannot be optimally processed into electrical energy. This potential development is able to support one of the goals of the Sustainable Development Goals (SDGs). Vertical axis wind turbines have advantages compared to horizontal axis wind turbines such as low noise, can work better in irregular wind flows and are able to rotate at low wind speeds. The maximum wind speed in 2020 around the Suramadu Bridge is 9.473 m/s while the largest ocean current speed is 1.1 m/s. This research uses Qblade software to design turbines and PSIM software to design power generation systems. The Darrieus H type turbine and the Darrieus Helixcoidate VAWT type turbine produce the most optimal turbine output power. The potential for wind turbine power at maximum speed is 4082,678 Watts, while the large potential for ocean current turbine power is 1253,149 Watts. The Cp value of the wind turbine is 0.49 while for the ocean current turbine it is 0.46. The radius and height of the wind turbine are 4m and 2m. Then the radius and height of the ocean current turbine are 2m and 1m. The Ld, Lq, Rs and Vpk/krpm of the generator are 1mH, 1mH, 1m? and 7112V/krpm. The simulation of wind power and ocean currents generates an electric power of 2072 Watt at a wind speed of 7m/s and an ocean current speed of 1m/s.